2022
DOI: 10.1186/s12859-022-04984-5
|View full text |Cite
|
Sign up to set email alerts
|

Study on the prognosis, immune and drug resistance of m6A-related genes in lung cancer

Abstract: Background Few studies have demonstrated that the relationship between m6A-related genes and the prognosis, tumor microenvironment and drug resistance of LC. Methods The main results were analyzed with bioinformatics methods. Results Hence, we found 10 m6A-related genes expressed less in tumor samples in comparison with normal ones. Using consensus clustering, all LC patients were grouped into 2 subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…was positive correlated with AHCY and cyclopamine was positive correlation with AHCY, while Erlotinib and STF-62247 were all nagtive correlation with BHMT, indicating that the one-carbon metabolism-related gene signature was related to drug sensitivity and COAD patients may bene t from these chemotherapy agents. In our study , drug sensitivity screen and validation showed that TGX221, a kind of PI3K-β inhibitor [49], might be the most potential drug in the one-carbon metabolism -dysregulated pathway.…”
Section: Discussionmentioning
confidence: 72%
“…was positive correlated with AHCY and cyclopamine was positive correlation with AHCY, while Erlotinib and STF-62247 were all nagtive correlation with BHMT, indicating that the one-carbon metabolism-related gene signature was related to drug sensitivity and COAD patients may bene t from these chemotherapy agents. In our study , drug sensitivity screen and validation showed that TGX221, a kind of PI3K-β inhibitor [49], might be the most potential drug in the one-carbon metabolism -dysregulated pathway.…”
Section: Discussionmentioning
confidence: 72%
“…In recent years, more and more studies have con rmed that m6A-related genes are closely related to malignant tumors. For example, ZC3H13, CBLL1, ELAVL1 and YTHDF1 are differentially expressed in lung cancer tissues, which is of great signi cance for the prediction and treatment of lung cancer [27].…”
Section: Discussionmentioning
confidence: 99%
“…m6A modification is reversibly modulated through the installation of methyl transferases (writers), the removal of a methyl group by demethylases (erasers), and the recognition of m6A binding proteins (readers) [ 22 , 23 ]. m6A writers and associated proteins (m6A writer complex) include Vir-like m6A methyl transferase-associated protein (VIRMA) [ 24 ], methyl transferase-like protein 3 (METTL3) [ 25 ], METTL4 [ 26 ], MTTL5 [ 27 ], METTL14 [ 28 ], METTL 16 [ 29 ], Wilms’ tumor 1 associated protein (WTAP) [ 30 , 31 ], RNA-binding motif protein 15/15B (RBM15/15B) [ 32 ], casitas B-lineage lymphoma-transforming sequence-like protein 1 (CBLL1) [ 33 ], zinc finger CCCH-type containing 13 (ZC3H13), and zinc finger CCHC-type containing 4 (ZCCHC4) [ 5 , 34 , 35 , 36 , 37 , 38 ]. RBM15/15B, VIRMA, CBLL1, ZCCHC4, and ZC3H13 act as associated proteins of m6A writers.…”
Section: Regulators Of Rna Methylationmentioning
confidence: 99%